8(2k+3)-2(-7k+7)=70

Simple and best practice solution for 8(2k+3)-2(-7k+7)=70 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 8(2k+3)-2(-7k+7)=70 equation:


Simplifying
8(2k + 3) + -2(-7k + 7) = 70

Reorder the terms:
8(3 + 2k) + -2(-7k + 7) = 70
(3 * 8 + 2k * 8) + -2(-7k + 7) = 70
(24 + 16k) + -2(-7k + 7) = 70

Reorder the terms:
24 + 16k + -2(7 + -7k) = 70
24 + 16k + (7 * -2 + -7k * -2) = 70
24 + 16k + (-14 + 14k) = 70

Reorder the terms:
24 + -14 + 16k + 14k = 70

Combine like terms: 24 + -14 = 10
10 + 16k + 14k = 70

Combine like terms: 16k + 14k = 30k
10 + 30k = 70

Solving
10 + 30k = 70

Solving for variable 'k'.

Move all terms containing k to the left, all other terms to the right.

Add '-10' to each side of the equation.
10 + -10 + 30k = 70 + -10

Combine like terms: 10 + -10 = 0
0 + 30k = 70 + -10
30k = 70 + -10

Combine like terms: 70 + -10 = 60
30k = 60

Divide each side by '30'.
k = 2

Simplifying
k = 2

See similar equations:

| 2*4.5= | | 2sin^3x+cos^2x=1 | | 2y-14=14x | | 8-6s=40 | | 6(2+6k)=-6(-7k-3) | | -(5x-1)+(2x+3)=17-(10x+1)+(x+6) | | 5*(x+3)-11=2x+19 | | x+38=2x+1 | | x^2-x-9xi-56-63i= | | f(5)=5-5 | | 17f+2=4f | | .5(8a+12)-27=15 | | p/8-1=7p/6+2 | | 40-2x=130-22x | | -3b+5b=2(2-b)+6(b-2) | | 4w+8=88 | | +2=7 | | (9x^4-6x^2+1)-(x^4-12x^3+34x^2+12x+1)=0 | | 2660+x(175.75)=5999.25 | | 72-x=86-2x | | -9+-5+14+-6= | | 5q+8=11 | | 2(3x+4y)=4x+2y | | 180-36-x=102 | | (13x-1)= | | 6+-4+-9+7= | | 0-8b=12 | | 4w+5z=6 | | 10x-1=1-4x | | 6y=5x+3 | | 3b+5b=2(2-b)+6(b-2) | | 3x-24=2x+35 |

Equations solver categories